European network of sport sciences in higher education
The European Network of Sport Sciences in Higher Education (ENSSHE) is a non-profit making association founded in 1991.The members of the ENSSHE (over 220) are institutes of Sport Sciences and sport organisations responsible for educational programmes and/or research in sport (see mission statement), located throughout the European Union. Those belonging to the European Economic Area, Middle and Eastern European countries have associate member status.